Pelaksanaan Metode Pembiasaan dalam Pendidikan Agama Islam untuk Meningkatkan Karakter Religius Peserta Didik di SMP Negeri 7 Padang - Azizah, Nabilla Nurul; Rahman, Rini (ANWARUL, 2023)
This study aims to analyze the application of the habituation method in Islamic Religious Education to improve the religious character of students at SMP Negeri 7 Padang. This research is included in the type of qualitative descriptive research with the type of field research (field research). Primary data in this study were obtained and processed directly from informants through observation, interviews and documentation. While the data analysis technique uses the theory of Miles and Huberman. The results of the study found that to improve the religious character of students through the habituation method, it was carried out through 5S activities (Smile, Greet, Greet, Polite, Polite), morning assemblies (praying and reading the Koran together in the field) prior to the teaching and learning process, midday prayers in congregation, cults Friday, and daily tahfidz. The form of evaluation of the habituation method to improve the religious character of Padang 7 Public Middle School students is through routine evaluations, direct evaluations, end of semester evaluations.